Pembelajaran Online Dengan Menulis Leaflet Teks Eksposisi untuk Menumbuhkan Sikap Peduli pada Lingkungan - Pujiasih, Erna (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2021)
Online Learning need creativities and innovation to face teaching problem that must continue in pandemic COVID19. Teacher is the key of success in education have important influence to teach the material for students to be care with the environment. English is as the compulsory lesson of Junior High School and Senior High School support to learning English and to educate care with the environment. Therefore teacher should use strategy to build the character of caring the environment. This paper will show how to teach online learning which the aim to increase the ability of students in writing leaflet of exposition and caring the environment. The teaching strategy can develop students participation online learning, creativity in writing leaflet, experience of online presentation and the student have the character of caring environment. Based on questioner data of 176 studentss, it found student got creativity, enjoying, interesting, inovatif model, increase the skill of writing exposition leaflet about environment and impove the creativity because it is the interesting design leaflet and the students have character in caring the environment